INVESTIGATION OF THE FIXED AMMONIUM CONTENT UNDER THE CONDITIONS OF LONG-TERM USE OF FERTILIZERS ON THE LUCHNO-CHRONZEM SOIL - Кудрявицька, Аліна; Карабач, Катерина (Modern engineering and innovative technologies, 2023)
The possibility of using fixed ammonium depends on the genesis of soils, their granulometric and mineralogical composition, as well as on agrotechnical measures - the system of application of ammonium and potassium fertilizers. It was established that the